The neurocognitive efficiency score: Derivation, validation, and application of a novel combination of concurrent electrophysiological and behavioral data. - Wenger, Michael J.; Townsend, James T.; Newbolds, Sarah F. (Cognitive, Affective & Behavioral Neuroscience, 2026)
Perceptual and cognitive effort require the expenditure of brain energy, and the efficiency of that energy expenditure can vary as a function of a range of exogenous and endogenous factors. The same is true for physical work, and tools have been developed to quantify energetic efficiency in the performance of physical work. The same is not true for the study of perceptual and cognitive effort. Here we draw on two lines of research – the formal characterization of workload capacity in perception and cognition, and the study of physical work – to propose a novel measure of neurocognitive efficiency. This neurocognitive efficiency score (NES) combines reaction time data with measures on concurrently acquired electroencephalographic (EEG) data to form a ratio that can be interpreted in terms of work accomplished relative to energy expended. We consider three measures on the EEG and show that one of them – global field power (GFP) – evidences a strong relationship to measures of metabolic energy expended. We then show how the NES can provide insights into differences in perceptual performance as a function of biological state. We argue that the NES has the potential for a wide range of applications in the study of effort exerted in perception and cognition in the context of factors including (but not limited to) aging, disease, stress, and differences in levels of expertise.